A comparison of palpation guided and ultrasound guided percutaneous biceps brachii tenotomy in dogs - Esterline, M. L.; Armbrust, L.; Roush, J. K. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The purpose of this study was to compare palpation guided and ultrasound guided techniques for biceps brachii tenotomy in dogs. The differences between the two tenotomy procedures in muscle incision length, confidence level of tenotomy, percentage tendon transection, difficulty of tendon location or transection, or amount of haemorrhage, were not significant. The ultrasound guided tenotomy procedure took significantly longer to perform and required a longer skin incision, but these differences were not considered to be clinically important. With palpation guided tenotomy, several surrounding muscular and tendinous structures were damaged. We concluded that ultrasound guided tenotomy is an accurate method of tendon identification because it allowed for complete transection in 10 out of 11 tendons, and provides a method for checking completeness of tendon transection after the procedure.
Keywords: Biceps tendon; ultrasound; tenotomy